Transient nucleation in selective laser melting of Zr-based bulk metallic glass - A. Ericsson; V. Pacheco; M. Sahlberg; J. Lindwall; H. Hallberg; M. Fisk (Materials & Design, 2020)
The crystallization rate during selective laser melting (SLM) of bulk metallic glasses (BMG) is a critical factor in maintaining the material's amorphous structure. To increase the understanding of the interplay between the SLM process and the crystallization behavior of BMGs, a numerical model based on the classical nucleation theory has been developed that accounts for the rapid temperature changes associated with SLM. The model is applied to SLM of a Zr-based BMG and it is shown that the transient effects, accounted for by the model, reduce the nucleation rate by up to 15 orders of magnitude below the steady-state nucleation rate on cooling, resulting in less nuclei during the build process. The capability of the proposed modelling approach is demonstrated by comparing the resulting crystalline volume fraction to experimental findings. The agreement between model predictions and the experimental results clearly suggests that transient nucleation effects must be accounted for when considering the crystallization rate during SLM processing of BMGs.